2020
DOI: 10.3390/ani10122326
|View full text |Cite
|
Sign up to set email alerts
|

Sicilian Black Pig: An Overview

Abstract: The Sicilian black pig (SB) (Nero Siciliano), also known as the Nero dei Nebrodi, Nero delle Madonie, or Nero dell’Etna pig ecotype, is an autochthonous Italian breed. The origins of this breed date back to Greek and Carthaginian dominations. In ancient times, its breeding was fairly common throughout Sicily, registering only a temporary reduction during the Arab domination. This breed is known primarily for its distinctive black coat, although some individuals display wattles and a partially or wholly white f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
5
12
0
Order By: Relevance
“…The mean value of MUFA obtained in this work was 5 to 6% higher than that obtained by other authors [ 5 , 42 ]. Similar values were also obtained for other breeds such as Nero Siciliano [ 63 ] and Prestice Black-Pied [ 68 ]. Regarding the PUFA content of backfat, values close to those reported by us were also found by other authors [ 63 , 68 ].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The mean value of MUFA obtained in this work was 5 to 6% higher than that obtained by other authors [ 5 , 42 ]. Similar values were also obtained for other breeds such as Nero Siciliano [ 63 ] and Prestice Black-Pied [ 68 ]. Regarding the PUFA content of backfat, values close to those reported by us were also found by other authors [ 63 , 68 ].…”
Section: Resultssupporting
confidence: 83%
“…The intramuscular MUFA content of LTL varied between 50.04% for the T2 treatment and 52.80% for treatment T3 and was within the values reported by other authors with the inclusion of 100 g/kg of olive cake [ 5 ] but lower than the 55.1% for the Swallow-bellied Mangalitsa and the 58% for the White Mangalitsa found for these two Serbia genotypes recognized as fatty pig breeds [ 41 ]. The MUFA content was within the values reported for different local breeds such as the Preto Alentejano breed [ 57 ], Iberian pigs [ 60 , 61 ], Mora Romagnola and Casertana breeds [ 62 ], Sicilian Black pig [ 63 ], Croatian native pig [ 58 ], Chinese Heigai pig [ 64 ] and Celta pigs [ 39 ]. This proportion of MUFA appears to be a trend in the autochthonous southern European swine breeds.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In this study, we provide the first metagenomic analysis of faecal samples collected from Sicilian pigs breed, whose meat is characterised by an average intramuscular fat content of 4.6% and high levels of 'good' fats (Zumbo et al 2020). Our data revealed that microbial taxa associated with this local breed follow, to some extent, the taxonomic pattern observed in other pig breeds worldwide (Bergamaschi et al 2020), although the prevalence of some dominant bacterial phyla (Firmicutes and Bacteroidetes) was clearly different (Patil et al 2020).…”
Section: Discussionmentioning
confidence: 67%